New Diplommatinidae from Sarawak, Malaysia (Borneo), of the genera Opisthostoma W.T. & H.F. Blandford, 1860 and Plectostoma H. Adams, 1865 (Gastropoda: Architaenioglossa: Diplommatinidae) - Jaap J., Vermeulen; Mohammad Effendi, Marzuki; Mohd Zacaery, Khalik (Basteria, 2022)
Six new species of the genera Opisthostoma W.T. & H.F. Blandford, 1860 and Plectostoma H. Adams, 1865 (Architaenioglossa, Diplommatinidae) are described from Sarawak (Malaysia), on the island of Borneo.